The Relationship Between Leadership Type, Work Motivation, Training of Employee, and Physical Work Environment Toward Employee’s Performance of Fastfood Company in Yogyakarta Indonesia - Guntoro, Budi (2016)
This research was aimed to analyze the leadership type, work motivation, employee’s training, physical work environment, and employee’s performance and the relationship between leadership type, work motivation, employee training, and physical work environment toward employee’s performance at Stores of Kentucky Fried Chicken ( KFC) Yogyakarta. The data were gathered in the stores KFC Yogyakarta using questionnaires that had been tested for its validity and reliability. Stores applied in this research were four stores; they were KFC BDNI, KFC Galleria, KFC Adi Sucipto and KFC Ambarukmo Plaza, while to test validity and reliability of the questionnaires in was KFC UGM. 76 Respondents were selected by census and then by their complete questionnaires. The data were statistically analyzed using the Chi-Square, Cramer's V and Spearman’s Correlation. The results showed that the leadership type of the manager of the store was supportive type. The majority of respondents had a high work motivation. The training of the employee was classified in medium category. All employees assessed that physical work environment was classified in comfortable category. Most of the Employee’s performance was in the high category. Employee’s performance had a correlation (P<0.01) with leadership type; employee’s performance had a correlation (P<0.01) with employee’s training; employee’s performance had a correlation (P<0.05) with physical work environment; and employee’s performance also had a correlation (P<0.10) with work motivation. Leadership type, work motivation, employee’s training, and physical work environment had a low strength correlation with employee’s performance